Overview of vending machine impact on food choices at university / Farah Nadzirah Mohd Basri - Mohd Basri, Farah Nadzirah (2020)
Vending machine that is made available inside the university campuses are bind to institution’s policy and the collaboration with outsource vendor which will eventually affecting the food availability in the vending machine. Student acceptance towards what is being put on sale will determine to revenue made by both the institution and the vendor.